Using Gabions to Protect Oil Storage Facilities from Damage - Biliaiev, M. M.; Kalashnikov , I. V.; Berlov, O. V.; Kozachyna, V. A.; Poltoratska, V. M. (Science and Transport Progress, 2024)
Purpose. During a drone explosion, debris is generated that poses a risk of damage to both humans and objects at an industrial site. Therefore, the main purpose of this study is to evaluate the effectiveness of using gabions with different fillers to reduce the risk of damage to the wall of an oil storage facility by debris generated during a drone explosion at an industrial site, as well as to analyze the value of the out-of-band velocity of the debris. Methodology. A numerical model based on the integration of the equation of motion of a material point was used to analyze the effectiveness of using gabions as protective structures of an oil storage facility during the flying of drone debris. The equations of motion of the debris are based on Newton's second law. This approach makes it possible to determine the unobstructed velocity of the fragment after passing the body of the protective barrier - the gabion. The developed numerical model takes into account the initial velocity of the fragment, its size, direction of movement, ejection height, and the material that fills the gabion body. On the basis of this numerical model, a computer program was created to conduct a computational experiment. Findings. An effective tool has been developed to analyze the risk of damage to the oil storage facility from the metallic impact of debris generated in the event of a drone explosion and to analyze the effectiveness of gabions. The results of computational experiments are presented. Originality. A fast-calculating numerical model has been built for the operational analysis of the efficiency of using gabions with different contents, which are used to protect an oil storage facility at an industrial site from the missile impact of debris generated by a drone explosion. Practical value. A computer program has been developed to calculate the dynamics of debris movement in the air and in the body of the gabion. The use of this program makes it possible to select the rational dimensions of a protective barrier - gabion at an industrial site to protect an oil storage facility from damage.